The impact of dissolved organic carbon and bacterial respiration on pCO2 in experimental sea ice. (February 2016) - Zhou, J.; Kotovitch, M.; Kaartokallio, H.; Moreau, S.; Tison, J.-L.; Kattner, G.; Dieckmann, G.; Thomas, D.N.; Delille, B.
Highlights: Brine concentration/dilution causes the largest temporal changes of pCO2 in ice. Elevated BR due to riverine DOC addition increases pCO2 in sea ice. Gas exchange and the buffer effect further affect the bacterial impact on pCO2 . Abstract: Previous observations have shown that the partial pressure of carbon dioxide (pCO2 ) in sea ice brines is generally higher in Arctic sea ice compared to those from the Antarctic sea ice, especially in winter and early spring. We hypothesized that these differences result from the higher dissolved organic carbon (DOC) content in Arctic seawater: Higher concentrations of DOC in seawater would be reflected in a greater DOC incorporation into sea ice, enhancing bacterial respiration, which in turn would increase the pCO2 in the ice. To verify this hypothesis, we performed an experiment using two series of mesocosms: one was filled with seawater (SW) and the other one with seawater with an addition of filtered humic-rich river water (SWR). The addition of river water increased the DOC concentration of the water from a median of 142 μmol Lwater − 1 in SW to 249 μmol Lwater − 1 in SWR. Sea ice was grown in these mesocosms under the same physical conditions over 19 days. Microalgae and protists were absent, and only bacterial activity has been detected. We measured the DOC concentration, bacterial respiration, total alkalinity and pCO2 in sea ice and the underlying seawater, and we calculated the changes in dissolved inorganic carbon (DIC) in both media. We found that bacterial respiration in ice was higher in SWR: median bacterial respiration was 25 nmol C Lice − 1  h −1 compared to 10 nmol C Lice − 1  h −1 in SW. pCO2 in ice was also higher in SWR with a median of 430 ppm compared to 356 ppm in SW. However, the differences in pCO2 were larger within the ice interiors than at the surfaces or the bottom layers of the ice, where exchanges at the air–ice and ice–water interfaces might have reduced the differences. In addition, we used a model to simulate the differences of pCO2 and DIC based on bacterial respiration. The model simulations support the experimental findings and further suggest that bacterial growth efficiency in the ice might approach 0.15 and 0.2. It is thus credible that the higher pCO2 in Arctic sea ice brines compared with those from the Antarctic sea ice were due to an elevated bacterial respiration, sustained by higher riverine DOC loads. These conclusions should hold for locations and time frames when bacterial activity is relatively dominant compared to algal activity, considering our experimental conditions.